Impact of a nutrition education programme on free sugar intake & nutrition-related knowledge in fifth-grade schoolchildren. (23rd November 2020) - Winzer, Eva; Wakolbinger, Maria; Schätzer, Manuel; Blagusz, Karin; Rieder, Anita; Lechleitner, Monika; Hoppichler, Friedrich
Abstract: Background: The objective was to evaluate a 5-week nutrition education programme (ACTION) in fifth-grade schoolchildren in Austria on free sugar intake, nutrition-related knowledge (NRK) and with the RE-AIM framework on the overall public health impact. Methods: A prospective case-controlled cohort (pre–post design) from seven secondary schools in Vienna tested programme efficacy. NRK was assessed with a 20-item questionnaire and dietary behaviour and free sugar intake with a semi-quantitative Food Frequency Questionnaire. A total of 12 intervention classes (IG) received the programme, conducted by teachers and integrated in the curriculum, and 6 control classes followed their usual curriculum. Results: In 344 children, aged 10.4 (0.8) years, free sugar intake decreased significantly over time in IG by 13% ( P =0.001) with a group difference of −10.1 (95% CI −18.8, −1.5; P =0.021) g/day. The food groups 'sweets & pastries', 'soft drinks', 'fast food' and 'salty snacks' mainly contributed to this reduction. Moreover, NRK increased significantly over time in IG with a group difference of 9.0% of correct answers (95% CI 5.8, 12.2; P <0.001; Cohen's d 0.57). The programme was disseminated to 10% of fifth-grade classrooms in Austrian secondary schools and to 12% in Vienna. Conclusions: The ACTION programme shows potential for public health impact with improving dietary behaviour as free sugar intake, NRK, and its dissemination. It required a minimum of money per schoolchild as the programme was conducted by teachers and was integrated in the curriculum.